Recombinant Zika Virus Subunits Are Immunogenic and Efficacious in Mice - To, Albert (mSphere, 2018)
Following the 2015 Zika virus (ZIKV) outbreaks in the South Pacific, Caribbean, and Americas, ZIKV has emerged as a serious threat due to its association with infantile microcephaly and other neurologic disorders. Despite an international effort to develop a safe and effective vaccine to combat congenital Zika syndrome and ZIKV infection, only DNA and mRNA vaccines encoding the precursor membrane (prM) and envelope (E) proteins, an inactivated-ZIKV vaccine, and a measles virus-based ZIKV vaccine are currently in phase I or II (prM/E DNA) clinical trials. A ZIKV vaccine based on a nonreplicating, recombinant subunit platform offers a higher safety profile than other ZIKV vaccine candidates but is still highly immunogenic, inducing high virus-neutralizing antibody titers. Here, we describe the production and purification of Drosophila melanogaster S2 insect cell-derived, soluble ZIKV E protein and evaluate its immunogenicity and efficacy in three different mouse strains. As expected, significant virus-specific antibody titers were observed when using formulations containing clinically relevant adjuvants. Immunized mice challenged with live virus demonstrate inhibition of virus replication. Importantly, plaque reduction neutralization tests (PRNTs) indicate the high-titer production of neutralizing antibodies, a correlate of protection in the defense against ZIKV infection. ZIKV challenge of immunocompetent mice led to full protection against viremia with two doses of adjuvanted vaccine candidates. These data demonstrate a proof of concept and establish recombinant subunit immunogens as an effective vaccine candidate against ZIKV infection. IMPORTANCE The recent outbreaks of Zika virus (ZIKV) infection in French Polynesia, the Caribbean, and the Americas have highlighted the severe neuropathological sequelae that such an infection may cause. The development of a safe, effective ZIKV vaccine is critical for several reasons: (i) the difficulty in diagnosing an active infection due to common nonspecific symptoms, (ii) the lack of a specific antiviral therapy, and (iii) the potentially devastating pathological effects of in utero infection. Moreover, a vaccine with an excellent safety profile, such as a nonreplicating, noninfectious vaccine, would be ideal for high-risk people (e.g., pregnant women, immunocompromised patients, and elderly individuals). This report describes the development of a recombinant subunit protein vaccine candidate derived from stably transformed insect cells expressing the ZIKV envelope protein in vitro, the primary antigen to which effective virus-neutralizing antibodies are engendered by immunized animals for several other flaviviruses; the vaccine candidate elicits effective virus-neutralizing antibodies against ZIKV and provides protection against ZIKV infection in mice.